First-time mothers’ experiences of pregnancy and birth following assisted reproductive technology treatment in Taiwan - Mei-Zen Huang; Yi-Chin Sun; Meei-Ling Gau; Shuby Puthussery; Chien-Huei Kao (Journal of Health, Population and Nutrition, 2019)
Abstract Background Assisted reproductive technology (ART) treatment tends to involve significant physical and emotional commitments that can impact maternal, infant, and family health and well-being. An in-depth understanding of experiences is necessary to provide adequate support for women and their families during pregnancy and transition to parenthood following ART treatment. The aim of this study was to explore first-time mothers’ experiences of pregnancy and transition to parenthood following successful ART treatment in Taiwan. Method Twelve first-time mothers who conceived and gave live birth using ART treatment were purposively selected from a fertility centre in Taipei, Taiwan. Women’s experiences in pregnancy and in their transition to motherhood were explored using semi-structured in-depth interviews. All interviews were recorded, transcribed, and analysed using the Colaizzi strategy. Results The mothers’ accounts reflected three main themes: ‘being different from mothers who became pregnant naturally’, ‘ensuring health and safety of the foetus’, and ‘welcoming new lives with excitement’. The difference mothers felt about themselves was evident in four subthemes: becoming pregnant after a long wait, feeling vulnerable during pregnancy, relying on family’s assistance and support, and worrying about the impact of ART on health. The theme on ‘ensuring health and safety of the foetus’ encompassed three subthemes: activities to protect the unborn baby, monitoring foetal movement constantly to maintain peace of mind, and receiving foetal reduction for the sake of the pregnancy. Narratives around ‘welcoming new lives with excitement’ reflected four subthemes: overcoming hardship for worthwhile results, realising one’s life and dreams, proving to be fertile enough to give birth, and return to normal life track. Conclusion Findings indicate the need for educational and psychosocial interventions to support women and their families physically and psychologically during ART treatment. The stigma related to infertility and the psychosocial support from family are aspects to consider while planning intervention programmes.